Media Ethics : issues and cases - Patterson, Philip; Wilkins, Lee. (New York : McGraw-Hill, 2014)
By combining real-life cases with a succinct introduction to ethical theory, this text helps prepare one for the ethical situations they will encounter in the media professions.--[book cover]
Includes bibliographical references (p. 293-303) and index.
Keywords: Mass media -- Moral and ethical aspects; Communication -- Moral and ethical aspects